A new approach of structural and chemical modification on graphene electrodes for high-performance supercapacitors. (April 2016) - Hwang, Yun-Hwa; Lee, Sun Min; Kim, Yong Jae; Kahng, Yung Ho; Lee, Kwanghee
Abstract: The low energy density of graphene-based supercapacitors has been a critical bottleneck for their commercialization. In particular, the poor capacitance due to the lack of electrically porous channels and insufficient Faradaic reactions in reduced graphene oxide (RGO) electrodes has been a major limiting factor for their successful application. Herein, we demonstrate an innovative process for modifying the electrode properties with well-interconnected porous channels and oxygen-functional groups (denoted as the PRGO-O electrode) achieved via a ZnO-template assisted by alkaline treatment at room temperature. The PRGO-O electrodes are dominated by hierarchical mesoporous structures located between the isolated macroporous RGO interlayers and arranged sequentially by oxygen-functional groups anchored on the surface of interconnected porous structures. Those synergetic effects of interconnected porous structures and oxygen-functionalization resulted in a specific capacitance of 322.1 F g −1 with a high energy density of 38.8 Wh kg −1 in two-electrode supercapacitor cells. This result provides a promising solution for designing high-capacitive and high-rate electrodes for high-performance energy storage devices.